К вопросу об устойчивости сопряжений капитальных выработок глубоких шахт - Раскидкин, В.В. (Геотехническая механика, 2011)
Наведений аналіз стану сполучень протяжних виробок. Розглянуті умови підтримання
похилих виробок та сполучень на шахті ім. В.М. Бажанова. Визначені розрахункові показники параметрів сполучень виробок. Наведені результати шахтних досліджень за станом
сполучень капітальних похилих виробок шахти ім. В.М. Бажанова. The analysis of the state of pairings of the extended workings is resulted. The terms of maintenance of the sloping workings and pairings are considered on a mine the name of V.M. Bazhanova. The calculation indexes of parameters of pairings of workings are certain. The results of the
mine researches are resulted after the state of pairings of the capital sloping workings of mine the
name of V.M. Bazhanova.